Review of PRGF-HIPC Financing, the Adequacy of the Reserve Account of the PRGF Trust, and Subsidization of Emergency Assistance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Provides the basis for the semi-annual decision on the adequacy of the Reserve Account of the PRGF Trust. It also updates the status of resources for financing PRGF operations and the HIPC Initiative and bilateral contributions to the subsidization of emergency assistance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Spain